Student’s Perspective on Reading Comprehension Through E-Learning at Senior High School - Novita Sari, Dahlia (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2023)
This research has the perspective of reading comprehension conducted at SMA N 14 Pekanbaru, the main focus of the study of E-learning reading comprehension based on the Whatsaap grub application, states that qualitative research is a research procedure that uses descriptive data in the form of writing or text. spoken words from observable persons or actors. Reading as one of the basic language skills has an important role in expanding one's knowledge to access information and use it. The high enthusiasm for learning is not limited to one's age, gender or occupation. Many workers still want to learn on the sidelines of their work activities. And this study aims to analyze students who study Reading Comprehension E-learning material using the WhatsApp grub application, on the results of the analysis the average total score in one class is 89.9%. From the results of the study it was found that the average student's ability to learn to read and understand using the WhatsApp Grub application method was classified as very good. In this case, in this case there were 20 (80%) students in the very good category, there were 4 (20%) students who were in the good category and none were in the low and bad categories.